Fkbp10 Deletion in Osteoblasts Leads to Qualitative Defects in Bone. (20th March 2017) - Lietman, Caressa D; Lim, Joohyun; Grafe, Ingo; Chen, Yuqing; Ding, Hao; Bi, Xiaohong; Ambrose, Catherine G; Fratzl‐Zelman, Nadja; Roschger, Paul; Klaushofer, Klaus; Wagermaier, Wolfgang; Schmidt, Ingo; et al.
ABSTRACT: Osteogenesis imperfecta (OI), also known as brittle bone disease, displays a spectrum of clinical severity from mild (OI type I) to severe early lethality (OI type II), with clinical features including low bone mass, fractures, and deformities. Mutations in the FK506 Binding Protein 10 ( FKBP10 ), gene encoding the 65‐kDa protein FKBP65, cause a recessive form of OI and Bruck syndrome, the latter being characterized by joint contractures in addition to low bone mass. We previously showed that Fkbp10 expression is limited to bone, tendon, and ligaments in postnatal tissues. Furthermore, in both patients and Fkbp10 knockout mice, collagen telopeptide hydroxylysine crosslinking is dramatically reduced. To further characterize the bone specific contributions of Fkbp10, we conditionally ablated FKBP65 in Fkbp10 fl/fl mice ( Mus musculus ; C57BL/6) using the osteoblast‐specific Col1a1 2.3‐kb Cre recombinase. Using μCT, histomorphometry and quantitative backscattered electron imaging, we found minimal alterations in the quantity of bone and no differences in the degree of bone matrix mineralization in this model. However, mass spectroscopy (MS) of bone collagen demonstrated a decrease in mature, hydroxylysine‐aldehyde crosslinking. Furthermore, bone of mutant mice exhibits a reduction in mineral‐to‐matrix ratio and in crystal size as shown by Raman spectroscopy and small‐angle X‐ray scattering, respectively. Importantly, abnormalities in bone quality were associated with impaired bone biomechanical strength in mutant femurs compared with those of wild‐type littermates. Taken together, these data suggest that the altered collagen crosslinking through Fkbp10 ablation in osteoblasts primarily leads to a qualitative defect in the skeleton. © 2017 American Society for Bone and Mineral Research.